FUNGSI REKAM MEDIK SEBAGAI UPAYA PERLINDUNGAN HUKUM BAGI DOKTER YANG MELAKUKAN TINDAKAN MEDIK - Ariq Ablisar; Mahmud Mulyadi; Muhammad Ekaputra; Mahmul Siregar (Universitas Sumatera Utara, 2018)
ABSTRACT The legal relationship between patients with doctors can occur among other things because the patient himself went to the doctor to help treat the pain he suffered, in circumstances such as this happens the approval of will between the parties, and going legal relationship sourced against the treatment process and the advice given by a physician will be achieved when doctors can hold a reciprocal communication to the patients. A doctor who is willing to listen to the opinions and complaints of the patient, the patient will cause more willing to comply with the process of healing effort so that the aim of the agreement, namely the healing can be achieved. Setting the standard of the medical profession and the standards of health services as well as medical record setting in Indonesia. A doctor can be called have done wrong medical actions, namely does not make medical record when the doctor does not carry out the treatment process in accordance with the standard Procedural Operations (SPO) which has been set up in the education medicine, and when the doctor does not exercise his profession in accordance with KODEKI, UUK, UUPK, UURS, PERMENKES. With relatively minimal understanding of lay society, it is difficult to differentiate between medical risks with malpractice. It is based on that of a cure for the disease is not only based on the actions of health workers, but is also influenced by other factors such as the possibility of complications, durability of the body that are not the same, the compliance in treatment the therapeutic Regimen